The Effectiveness of the Ma'baca Baca Tradition as An Educational Medium on Pregnancy Danger Signs to Prevent Stunting” - Devi Darwin; Sugiyanto Sugiyanto; Herawati Syamsul; Yulianti N.; Hasri Hasri; Kristi Magdalena Dowo (Indonesian Journal of Global Health Research, 2026)
Stunting remains a serious public health problem, with inadequate maternal knowledge of pregnancy danger signs being one of its major risk factors. Health education efforts are often less effective due to the lack of culturally appropriate approaches. The Ma’baca-Baca tradition, which is deeply rooted in the Luwu indigenous community, has strong potential as a culturally acceptable medium for health education. Therefore, integrating education on pregnancy danger signs and stunting prevention into the Ma’baca-Baca tradition, supported by a pocketbook as a sustainable source of information, is important to examine in order to improve the effectiveness of culturally based maternal health education. To determine the effectiveness of the Ma'baca Baca tradition as an educational medium on pregnancy danger signs for stunting prevention in the Luwu indigenous community. This study employed a quasi-experimental design using a pre-test and post-test with a control group. The participants were women from religious study groups selected through accidental sampling, namely those who attended the Ma’baca-Baca activity. The respondents consisted of 25 participants in the intervention group who received education through a pocketbook and 25 participants in the control group. Data were collected through pre-tests and post-tests and analyzed using the Mann–Whitney test. A normality test was conducted, and the results showed that the data were not normally distributed. Data analysis was performed using the Mann-Whitney test, which revealed a p-value of 0.001 (< 0.05), indicating a statistically highly significant difference between the intervention group and the control group after the intervention was administered. These results demonstrate that the intervention was effective in improving pregnant women’s knowledge of pregnancy danger signs. In other words, the treatment applied to the intervention group was proven to have a significantly positive impact compared to the control group.